The Influence of Tiktok Influencers and Social Media on Impulsive Buying on Skintific - Wahyu Fitriyansyah; Puti Kayimani Josika (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of TikTok Influencers and social media on consumers' impulsive buying behavior regarding Skintific products. TikTok has evolved into an e-commerce platform through the TikTok Shop feature, leveraging influencer-based marketing strategies. Influencers with high credibility can influence consumers' purchasing decisions through engaging content and persuasive promotions. Additionally, the increasing use of social media plays a role in shaping impulsive shopping behavior, particularly among young generations. This research employs a quantitative method with purposive sampling techniques on 300 respondents who have purchased Skintific products after seeing promotions on TikTok. The regression analysis results show that TikTok Influencers and social media significantly affect impulsive buying, although their contribution is only 13.1%. This indicates that other more dominant factors influence consumers' impulsive buying behavior.